Classification, parameter estimation, and state estimation : an engineering approach using MATLAB - Heijden, Ferdinand van der (Wiley, 2004)
Classification, Parameter Estimation and State Estimation is a practical guide for data analysts and designers of measurement systems and postgraduates students that are interested in advanced measurement systems using MatLab. 'Prtools' is a powerful MatLab toolbox for pattern recognition and is written and owned by one of the co-authors, B.